Influence of Se doping on recently synthesized NaInS2-xSex solid solutions for potential thermo-mechanical applications studied via first-principles method. (March 2021) - Hossain, M.M.; Ali, M.A.; Uddin, M.M.; Hossain, M.A.; Rasadujjaman, M.; Naqib, S.H.; Nagao, M.; Watauchi, S.; Tanaka, I.
Highlights: Mechanical and thermal properties have been studied using first-principles method. NaInS2-x Sex (x = 0.5 and 1.5) shows damage tolerant properties while NaInS2-x Sex (x = 0, 1 and 2) are brittle in nature All compounds are easily machinable by the conventional cutting tools. NaInS2-x Sex (x = 0.5 and 1.5) compounds can be used as promising thermal barrier coating materials. Abstract: In the present work, the structural and hitherto unexplored thermal and mechanical properties of NaInS2-x Sex (x = 0, 0.5, 1.0, 1.5 and 2.0) compounds have been studied using the density functional theory. Besides, the elastic anisotropy indices and hardnesses of NaInS2-x Sex have been investigated as Se content is varied. The mechanical stability of all the compounds under study has been confirmed. The ratio of shear to bulk modulus ( G/B ) is low suggesting that the NaInS2-x Sex (x = 0.5 and 1.5) compounds exhibit damage tolerant (ductility) properties while rest of the compositions are brittle in nature. The predicted hardness ( H ) values are also influenced with the Se content in the following order: H (NaInSSe) > H (NaInS2 ) > H (NaInSe2 ) > H (NaInS1.5 Se0.5 ) > H (NaInS0.5 Se1.5 ). All the anisotropic indices under study indicate that NaInS2-x Sex compounds are anisotropic in nature. The Mulliken bond population analysis suggests that the degree of covalency of In-S/Se bonds decreases when S is substituted by Se. The origin of low Debye temperature ( Θ D ) and low minimum thermal conductivity ( K min ) have been successfully explained by considering the mean atomic weight ( M / n ) and average bond strength of the compounds. Temperature dependence of heat capacities ( C v, C p ) and linear thermal expansion coefficient ( α ) are also estimated using the quasi-harmonic Debye model and discussed. The low values of K min, Θ D and α and damage tolerant behavior clearly indicate that the NaInS2-x Sex (x = 0.5 and 1.5) compounds can be used as promising thermal barrier coating materials for high temperature applications.